2008
DOI: 10.1111/j.1439-0418.2008.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the efficacy of entomopathogenic nematode species at reducing western corn rootworm larvae and root damage in maize

Abstract: The western corn rootworm (Diabrotica virgifera virgifera LeConte, Coleoptera: Chrysomelidae) is an invasive maize (Zea mays L.) pest in Europe. Crop yield is significantly impacted by the feeding of all three larval instars on maize roots, making them prime targets for control measures. Therefore, the control efficacy of three entomopathogenic nematodes (EPNs), Steinernema feltiae (Filipjev), Heterorhabditis bacteriophora Poinar, and H. megidis Poinar, Jackson and Klein (Nematoda: Rhabditida), was studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 37 publications
(83 reference statements)
2
58
1
Order By: Relevance
“…To ''restore'' E␤C emission and test its importance for root protection under realistic field conditions, a maize variety that normally does not emit this compound was transformed with a gene from oregano (Origanum vulgare). We then compared WCR-inflicted root damage and beetle survival on transformed and nontransformed lines in the presence and absence of EPNs (25,30).…”
Section: Figmentioning
confidence: 99%
“…To ''restore'' E␤C emission and test its importance for root protection under realistic field conditions, a maize variety that normally does not emit this compound was transformed with a gene from oregano (Origanum vulgare). We then compared WCR-inflicted root damage and beetle survival on transformed and nontransformed lines in the presence and absence of EPNs (25,30).…”
Section: Figmentioning
confidence: 99%
“…A number of Þeld studies have found that soilapplied entomopathogenic nematodes in the genera Steinernema and Heterorhabditis, and entomopathogenic fungi in the genus Metarhizium, reduce rootworm survival and root injury (Wright et al 1993, Krueger and Roberts 1997, Toepfer et al 2008). In 2010, when rootworm abundance was high, the community of entomopathogens reduced April 2013 PETZOLDÐMAXWELL ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Field trials have shown that entomopathogens can reduce rootworm survival and injury to maize roots, and in some cases, increase yield (Wright et al 1993, Krueger and Roberts 1997, Journey and Ostlie 2000, Toepfer et al 2008). For example, the nematode Heterorhabditis bacteriophora Poinar significantly reduced root injury caused by western corn rootworm in a Þeld study by 14 Ð54% (Toepfer et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Thurston and Yule (1990), testing the nematodes S. feltiae All and S. bibionis Sn against D. barberi larvae in the field, in corn culture, observed that both species of EPNs tested reduced the number of larvae in the soil compared to the control, at concentrations of 1.3 x 10 8 Survival of larval (%) Virulence of entomopathogenic nematodes... 1155 and 1.3 x 10 9 IJ/ha, not verifying a difference among the species or the tested concentrations. Toepfer et al (2008), working with EPNs for the control of D. v. virgifera larvae under field conditions in the corn culture, verified that all of the species of nematodes (H. bacteriophora, S. feltiae and H. megidis) tested caused reduction of the insect population in the soil. However, the most virulent species was H. bacteriophora, that caused an 81% reduction.…”
Section: Susceptibility Of D Speciosa Larvae To Entomopathogenic Nemmentioning
confidence: 99%